THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP AND ORGANIZATIONAL CULTURE ON JOB SATISFACTION IN MILLENNIAL EMPLOYEES IN BANDAR LAMPUNG - Almira Devita Putri; Agung Juliansyah; Emi Suwarni (Jurnal REKOMEN (Riset Ekonomi Manajemen), 2023)
This study aims to determine the influence of Transformational Leadership and Organizational Culture on Job Satisfaction of Millennial employees in Bandar Lampung. The population in this study is the all-millennial employees in Bandar Lampung and the sample took the entire population using the non-probability sampling method using the incidental sampling method, sampling techniques based on intuition, i.e., anyone who is well literate and suitable with the criteria can be used as a sample. In this research, Slovin’s formula sample calculation was used so that a sample of 399 employees. The results of the study show that the transformational leadership variable has no significant effect on the job satisfaction of millennial employees in Bandar Lampung. The organizational culture variable has a significant influence on the job satisfaction of millennial employees in Bandar Lampung. The results of the study also show that transformational leadership and organizational culture simultaneously have a positive and significant effect on the job satisfaction of Millennial employees in Bandar Lampung. Meanwhile, based on the coefficient of determination (R2) of 0.487 or 48.7%. This shows that 48.7% of the variable job satisfaction can be influenced by transformational leadership (X1) and organizational culture (X2). While the remaining 51.3% is found in other variables that are not present or not examined in this study